Five years from now eaudiobook - Toon, Paige (Books on Tape, 2023)
BEST FRIENDS. FIRST KISS. FIRST LOVE. FIVE YEARS FROM NOW, WHAT WILL THEY BE? “Paige Toon's romances are powerful and poignant and never fail to leave me clutching her book to my chest.” – MIA SHERIDAN, author of ARCHER’S VOICE In the spirit of Mia Sheridan , a heartbreaking story of star-crossed, fated love, and two people who are brought together and torn apart every five years until they must make a choice that’s bigger than their lives alone. Nell and Van meet as children when their parents fall in love. They become best friends and each other’s whole world. Then tragedy strikes and Van is sent to the other side of the globe. Five years later, they find each other again. But they’re no longer children and the bond between them smolders into flames. New feelings surprise them both. They are destined, soulmates. Until an untimely discovery tears them apart again. For the next two decades, fate brings Nell and Van together every five years, even as life and circumstance divide them. They will have to make a choice, but it’s bigger than their lives alone. Is it bigger than their love?